National success in elite sport. Exploring the factors that lead to success - Nassif, N.; Raspaud, M. (Palgrave Macmillan, 2023)
This book takes a deep dive into the factors that lead to countries` success in elite sport. While some researchers have suggested looking at the political, economic, demographic, geographic and cultural characteristics of a country, other scholars have advocated that meso-level strategies such as financial support, governance, and talent identification systems are the factors that need to be taken into consideration. Taking into account the two sides of this debate, the authors review and evaluate these various components. They go on to use this review to propose a new holistic framework of analysis that includes the macro, meso and micro-level factors that lead to national success in elite sport. This is a valuable resource for researchers and students interested in sport management, particularly the subject of sport governance. In addition, sports consultants and policymakers will find this to be an eye-opening read.